Vineyard calcium sprays induce changes in grape berry skin, firmness, cell wall composition and expression of cell wall-related genes - Martins, Viviana (2020)
Supplementary data to this article can be found online at https://doi.org/10.1016/j.plaphy.2020.02.033.